Fiscal policy, entry and capital accumulation: Hump-shaped responses - Paulo Brito; Huw Dixon (Cardiff University, Cardiff Business School, 2012)
In this paper we consider the entry and exit of firms in a Ramsey model with capital and an endogenous labour supply. At the firm level, there is a fixed cost combined with increasing marginal cost, which gives a standard U-shaped cost curve with optimal firm size. The costs of entry (exit) are quadratic in the flow of new firms. The number of firms becomes a second state variable and the entry dynamics gives rise to a richer set of dynamics than in the standard case: in particular, there is likely to be a hump shaped response of output to a fiscal shock with maximum impact after impact and before steady-state is reached. Output and capital per firm are also likely to be hump shaped.
Keywords: E22; D92; E32; D92; 330; entry; Ramsey; fiscal policy; macroeconomic dynamics